The Strategic Trade Policies: Commercial Disputes on the World Aircraft Market - Liviu-George Maha; Sorin-Stefan Maha (CES Working Papers, 2012)
The paper aims to illustrate how strategic trade policy is used by analyzing the concrete situation in the world aircraft industry, focusing on the case of the large civil aircrafts and on the regional jet aircrafts. We want to clarify which is the position of GATT / WTO regarding the strategic trade policy, what are the factors which made it possible to use strategic trade policy in the aviation industry and how the strategic trade policy was implemented by the four major market actors considered, the disputes that have arisen from the use of strategic trade policy and how these were resolved.
Keywords: F12; F13; F14; F42; F53; 330; strategic trade policy; oligopoly; subsidies; multilateral system; countervailing measures Romania